Developing a State University System Model to Diversify Faculty in the Biomedical Sciences - Cresiski, Robin Herlands; Ghent, Cynthia Anne; Rutledge, Janet C.; Carter-Veale, Wendy Y.; Aumiller, Jennifer; Bertot, John Carlo; Enekwe, Blessing; Golembewski, Erin; Medina, Yarazeth; Scott, Michael S. (Frontiers in Psychology, 2022)
Amid increasing demands from students and the public, universities have recently reinvigorated their efforts to increase the number of faculty from underrepresented populations. Although a myriad of piecemeal programs targeting individual recruitment and development have been piloted at several institutions, overall growth in faculty diversity remains almost negligible and highly localized. To bring about genuine change, we hypothesize a consortia approach that links individuals to hiring opportunities within a state university system might be more effective. Here we present a case study describing the progress of the NSF-funded Alliances for Graduate Education and the Professoriate (AGEP) PROMISE Academy Alliance, a consortium within the University System of Maryland collaborating to develop, implement, self-study, evaluate and disseminate a unique postdoc-to-faculty conversion model in the biomedical sciences. The initiative centers on diversifying faculty across five institutions in the USM, including teaching-focused institutions, comprehensive universities, research institutions, and professional schools. Components of this approach include 1) enhanced recruiting and hiring practices to attract outstanding postdoctoral scholars from underrepresented backgrounds, 2) multi-institutional networking and professional development, and 3) a facilitated processes to transition (or “convert”) postdocs into tenure-track positions at their postdoctoral institution or another institution in the state system. This model is distinct from more deficit-based approaches because it goes beyond focusing on building the individual’s skills to enter the professoriate. This program restructures the traditionally short-term nature of postdoctoral employment and incorporates a pathway to a tenure-track professorship at the same institution or within the same statewide system where the postdoc is trained. This multi-institutional model leverages collaboration and distinct institutional strengths to create cross-institutional support, advocacy, and policy. Importantly, it uses a decentralized financial structure that makes this approach distinctly replicable. Recognizing the immediate need for more collaborative approaches to diversify faculty and a lack of literature about such approaches, this case study describes the development of, and potential benefits of, a state university system, as well as the qualitative lessons learned from self-study, internal evaluation, external evaluation, and NSF site visits. The AGEP PROMISE Academy can serve as a model for replication at other university systems hoping to diversify their faculty.